The role of educational and clinical prevention of dental diseases in older preschool children in a preschool - N. P. Vanchakova; S. B. Ulitovsky; I. V. Telnyuk; A. Yu. Guliev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2013)
A study of 19 preschool children (8 ofthem with speech disorders, 19 parents, 4 preschool teacher were to identify low hygienic knowledge and skills of parents and children. Children in violation of the formation of speech found in the playback lag motor tasks on the space-time parameters, broke a sequence of elements of action, lowered its component parts, the longer formulated phrase. What to consider when creating training programs for oral health.